The devoloping of studying learning culture and the developing of ICT in pandemic covid-19 in junior high school of rambutan - Roslina Roslina; Edi Harapan; Dessy Wardiah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The developing of studying-learning culture in Indonesia nowadays is increased in pandemic era of covid-19, we must face it because this corona virus spread almost in the whole of countries in the world, including Indonesia which have 34 provinces. Having connected with coronavirus, the education that we as Teacher face to the students of course will be problem, the Indonesia Government finally decide to do online class, we call it daring class and using of Information and Communication Technology (ICT) through internet, the students and the teachers have to stay at home , but they are able to learn their lessons via on line by using mobile phone application . Unlucky the students who are from the rich one can do it, they buy the pulse and quota easily but not for the poverty students who can’t buy it , it is the obstacle for our education minister to solve the way to help every students in Indonesia doing the education activities. Of course this process doing learning studying so far can run well enough , though we face this pandemic, we really hope it can be over sooner.